2015
DOI: 10.18869/acadpub.irjns.1.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Multiforme: A Single Hospital Experience

Abstract: Background & Aim: Glioblastoma multiforme (GBM), the highest grade glioma (grade IV), is the most malignant form of astrocytoma in adults. This study aimed at evaluating the relationship between demographic, clinical and medical factors with GBM outcome. Methods & Materials/Patients: Through a cross-sectional design, 58 patients with newly diagnosed GBM were studied from 1999 to 2015 in Guilan province (North of Iran). Demographic, clinical and medical data including age, gender, score of Karnofsky Performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
1
1
Order By: Relevance
“…Current epidemiological data show differences between males and females regarding the incidence of glioblastomas, with a male to female ratio ranging between 1.09:1 and 1.6:1 (Table 2). 5,[9][10][11][12][13][14][15][16][17] In contrast with these data, we found a relatively equal distribution between genders.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Current epidemiological data show differences between males and females regarding the incidence of glioblastomas, with a male to female ratio ranging between 1.09:1 and 1.6:1 (Table 2). 5,[9][10][11][12][13][14][15][16][17] In contrast with these data, we found a relatively equal distribution between genders.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly to other reports (Table 3), 5,[12][13][14]16 we found glioblastomas in the frontal, temporal, and parietal lobes. In a cohort of patients from Denmark, Hansen et al found glioblastomas located predominantly in the temporal lobe.…”
Section: Discussionsupporting
confidence: 91%
“…Gliomas account for almost 27% of brain tumors and the overall incidence of malignant glioma is 7.2 per 100,000 in general population [ 1 ]. According to the report of National Cancer Registry (NCR) in Iran, the overall incidence rate for malignant brain tumors is 2.74 per 100,000 in general population and high grade gliomas are 60.4% of the primary malignant registered brain tumors [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%